THE USED OF A MEDIUM OF LEARNING SONG FOREIGN LANGUAGE IN LEARNING SPEAK STRANGER IN ELEMENTARY SCHOOL - Amanda Nabila Yusuf (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
In support of an effective and efficient learning process, teachers need to determine how to strategize in appropriate learning. One of the strategies used in foreign language learning is to use learning media, but most teachers do conventional learning without using any learning media. Song is one of the appropriate learning media in language learning especially foreign languages. The purpose of this paper is to show the benefits of using learning media for foreign language songs in foreign language learning at elementary school so the teacher can switch to using effective learning media. The results obtained from the study of this article is that the use of songs on strengthening foreign language skills is recommended because it can help students master 2 of 4 skills, namely listening and speaking. Learners are also more motivated by the use of Song Media in learning because songs create a learning environment that is not boring. Although search websites about songs in learning are declining, but until now it is still sought and quite attractive to the public.